Identification of the Fungal Community in Otomycosis by Internal Transcribed Spacer Sequencing - Gu, Xiaona; Cheng, Xiangrong; Zhang, Jinhua; She, Wandong (Frontiers in Microbiology, 2022)
We used Internal Transcribed Spacer (ITS) sequencing to identify the fungal community in otomycosis patients and to evaluate the treatment effects of bifonazole. Ten patients who visited the Department of Otolaryngology of Jiangsu Provincial Hospital on Integration of Chinese and Western Medicine from May 2020 to April 2021 were recruited. Otomycosis patients were treated with bifonazole solution once a day for 14 days. Samples collected from the external auditory canal before and after treatment (Pre-treatment, n = 14 ears; Post-treatment, n = 14 ears) were used for microscopic examination, fungal culture, and ITS sequencing. Samples collected from ten volunteers (Control, n = 20 ears) were used as controls. The symptoms, including ear itching, aural fullness, otalgia, hearing loss, and physical signs were recorded before treatment as well as on the 7th and 14th days after treatment. Aspergillus was identified as a main pathogenic fungus by microscopic examination, fungal culture and ITS sequencing. At the genus level, Aspergillus was more abundant in the pre-treatment group than the control and post-treatment groups, and Malassezia was more abundant in the control and post-treatment groups than the pre-treatment group. The fungal species richness and diversity reduced significantly in the pre-treatment group compared with the control and post-treatment groups. The effective rate of bifonazole was 64.29% and 100% on the 7th and 14th days after treatment, respectively. In conclusion, the results obtained from morphologic studies and ITS sequencing indicate that Aspergillus is the main pathogenic fungus of otomycosis patients in Nanjing, Jiangsu Province, China. Malassezia is the dominant resident fungi in healthy individuals. ITS sequencing provides comprehensive information about fungal community in otomycosis and is helpful in evaluating the efficacy of antifungal agents.